How is Anxiety Identified and Diagnosed in Individuals with Autism Spectrum Disorder and Intellectual Disability? A Scoping Review. Issue 3 (31st October 2019) - Appleton, Helen; Roberts, Jacqueline; Simpson, Kate
ABSTRACT: Introduction : Individuals with Autism Spectrum Disorder display a pattern of social communication deficits and restricted and repetitive behaviors that leave them particularly vulnerable to developing anxiety. The presence of a co-occurring Intellectual Disability further complicates the situation, compromising traditional diagnostic techniques and processes. The dual diagnosis of ASD and ID appears to result in specific behavioral patterns that affect the way anxiety is identified in this population. Method : A scoping review was undertaken to explore what is currently known about the way anxiety is identified and diagnosed in individuals with ASD and ID. Results : In the limited research available consistent themes of difficulties with the diagnostic process, inconsistencies among measurement tools and the need to consider behavioral symptomology were found. Conclusion : Further research needs to be conducted to enhance our understanding of how anxiety is identified in those with ASD and ID. This research could more accurately inform reliable diagnostic processes and lead to better treatment and outcomes for this population.